2-Arylquinolines as novel anticancer agents with dual EGFR/FAK kinase inhibitory activity: synthesis, biological evaluation, and molecular modelling insights. (1st January 2022) - Elbadawi, Mostafa M.; Eldehna, Wagdy M.; Abd El-Hafeez, Amer Ali; Somaa, Warda R.; Albohy, Amgad; Al-Rashood, Sara T.; Agama, Keli K.; Elkaeed, Eslam B.; Ghosh, Pradipta; Pommier, Yves; Abe, Manabu
Abstract: In this study, different assortments of 2-arylquinolines and 2, 6-diarylquinolines have been developed. Recently, we have developed a new series of 6, 7-dimethoxy-4-alkoxy-2-arylquinolines as Topoisomerase I (TOP1) inhibitors with potent anticancer activity. Utilising the SAR outputs from this study, we tried to enhance anticancer and TOP1 inhibitory activities. Though target quinolines demonstrated potent antiproliferative effect, specifically against colorectal cancer DLD-1 and HCT-116, they showed weak TOP1 inhibition which may be attributable to their non-coplanarity. Thereafter, screening against kinase panel revealed their dual inhibitory activity against EGFR and FAK. Quinolines 6f, 6h, 6i, and 20f were the most potent EGFR inhibitors (IC50 s = 25.39, 20.15, 22.36, and 24.81 nM, respectively). Meanwhile, quinolines 6f, 6h, 6i, 16d, and 20f exerted the best FAK inhibition (IC50 s = 22.68, 14.25, 18.36, 17.36, and 15.36 nM, respectively). Finally, molecular modelling was employed to justify the promising EGFR/FAK inhibition. The study outcomes afforded the first reported quinolines with potent EGFR/FAK dual inhibition. Graphical Abstract: UF0001